Catalytic Oxidation of Alkanes and Alkenes by H2O2 with a μ‐Oxido Diiron(III) Complex as Catalyst/Catalyst Precursor. Issue 21 (17th July 2015) - Das, Biswanath; Al‐Hunaiti, Afnan; Haukka, Matti; Demeshko, Serhiy; Meyer, Steffen; Shteinman, Albert A.; Meyer, Franc; Repo, Timo; Nordlander, Ebbe
Abstract: A new μ‐oxo diiron(III) complex of the lithium salt of the pyridine‐based unsymmetrical ligand 3‐[(3‐{[bis(pyridin‐2‐ylmethyl)amino]methyl}‐2‐hydroxy‐5‐methylbenzyl)(pyridin‐2‐ylmethyl)amino]propanoate (LiDPCPMPP), [Fe2 (μ‐O)(LiDPCPMPP)2 ](ClO4 )2, has been synthesized and characterized. The ability of the complex to catalyze oxidation of several alkanes and alkenes has been investigated by using CH3 COOH/H2 O2 (1:1) as an oxidative system. Moderate activity in cyclohexane oxidation (TOF = 33 h –1 ) and good activity in cyclohexene oxidation (TOF = 72 h –1 ) were detected. Partial retention of configuration (RC = 53 %) in cis ‐ and trans ‐1, 2‐dimethylcyclohexane oxidation, moderate 3°/2° selectivity (4.1) in adamantane oxidation, and the observation of a relatively high kinetic isotope effect for cyclohexane oxidation (KIE = 3.27) suggest partial metal‐based oxidation, probably in tandem with free‐radical oxidation. Low‐temperature UV/Vis spectroscopy and mass spectrometric studies in the rapid positive detection mode indicate the formation of a transient peroxido species, [Fe2 (O)(O2 )(LiDPCPMPP)2 ] 2+, which might be an intermediate in the metal‐based component of the oxidation process. Abstract : A μ‐oxido diiron(III) complex, [Fe2 (μ‐O)(LiDPCPMPP)2 ](ClO4 )2, was synthesized and characterized. This complex was used as catalyst in C–H bond oxidation with CH3 COOH–H2 O2 as chemical oxidant. Reactivity studies indicate that the oxidation process goes through a metal‐based mechanism concomitant with a radical process.